Combinations of Single-Gene Biomarkers Can Precisely Stratify 1,028 Adult Gliomas for Prognostication - Chan, Aden Ka-Yin; Shi, Zhi-Feng; Li, Kay Ka-Wai; Wang, Wei-Wei; Chen, Hong; Chung, Nellie Yuk-Fei; Chan, Danny Tat-Ming; Poon, Wai-Sang; Loong, Herbert Ho-fung; Liu, Xian-Zhi; Zhang, Zhen-Yu; Mao, Ying; et al. (Frontiers in Oncology, 2022)
Advance genomic techniques have now been incorporated into diagnostic practice in neuro-oncology in the literature. However, these assays are expensive, time-consuming and demand bioinformatics expertise for data interpretation. In contrast, single gene tests can be run much more cheaply, with short turnaround time and are available in general pathology laboratories. The objective of this study was to establish a molecular grading scheme for adult gliomas using combinations of commonly available single-gene tests. We retrospectively evaluated molecular diagnostic data of 1,275 cases of adult diffuse gliomas from three institutions where we were testing for IDH1/2 mutation, TERTp mutation, 1p19q codeletion, EGFR amplification, 10q deletion, BRAF V600E and H3 mutations liberally in our regular diagnostic work-up. We found that a molecular grading scheme of Group 1 (1p19q codeleted, IDH mutant), Group 2 (IDH mutant, 1p19q nondeleted, TERT mutant), Group 3 (IDH mutant, 1p19q nondeleted, TERT wildtype), Group 4 (IDH wildtype, BRAF mutant), Group 5 (IDH wildtype, BRAF wildtype and not possessing the criteria of Group 6), and Group 6 (IDH wildtype, and any one of TERT mutant, EGFR amplification, 10q deletion or H3 mutant) could significantly stratify this large cohort of gliomas for risk. 1,028 (80.6 %) cases were thus classifiable with sufficient molecular data. There were 270 cases of molecular Group 1, 59 cases of molecular Group 2, 248 cases of molecular Group 3, 27 cases of molecular Group 4, 117 cases of molecular Group 5, and 307 cases of molecular Group 6. The molecular Groups were independent prognosticators by multi-variate analyses and in specific instances, superseded conventional histological grades. We were also able to validate the usefulness of the Groups with a cohort retrieved from TCGA where similar molecular tests were liberally available. We conclude that a single gene molecular stratification system, useful for fine prognostication, is feasible and can be adopted by a general pathology laboratory.